SOCIAL CAPITAL AND THE LOCAL DEVELOPMENT POLICY UNDER THE LEADER PROGRAMME IN POLAND - Chmieliński, Paweł (Economics of Agriculture, 2018)
The paper presents the premises for the social capital formation in rural areas, based on the analysis of Axis IV Leader measures. Outcomes of the survey conducted among 72 local action groups members stresses the necessity to strengthen the legal power of LAGs in supporting bottom-up initiatives through implementation of measures aimed directly to local community members. This would allow for establishing the positive relations of LAGs with smaller entities, and with the local community, and increase the ability in social capital creation in rural areas.